Peer-Led Nutritional Education Plus Iron-Folic Acid for Adolescent Iron-Deficiency Anemia: A Cluster Randomized Controlled Trial in Indonesia - Indri Yani Septiana; Annisa Annisa (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Iron-deficiency anemia affects roughly one-third of adolescent girls and, by entering reproductive life with depleted iron stores, propagates intergenerational maternal risk. Standard weekly iron-folic acid (IFA) supplementation is undermined by poor adherence. We evaluated whether adding a peer-led nutritional-education program to IFA improves hematologic and psychosocial outcomes more than IFA alone. Methods: In a single-blind, parallel-group cluster randomized controlled trial in urban Palembang, Indonesia, 16 school clusters were randomized 1:1 to peer-led education plus weekly IFA (60 mg iron, 2.8 mg folic acid) or IFA alone. We enrolled 320 post-menarcheal girls aged 13–17 years with baseline hemoglobin 8.0–11.9 g/dL. Co-primary outcomes were hemoglobin and serum ferritin; the secondary outcome was the WHO-5 Well-Being Index, assessed at baseline, 3 and 6 months. Generalized linear mixed models with cluster random intercepts (intention-to-treat) were used. Results: At 6 months the intervention produced adjusted mean differences of +1.42 g/dL hemoglobin (95% CI 1.05–1.79; Cohen's d 2.11), +13.5 µg/L ferritin (10.2–16.8; d 2.75) and +23.4 WHO-5 points (19.8–27.0; d 3.14), all p<0.001. Anemia resolved in 89.3% versus 33.1% (RR 2.70, 95% CI 2.13–3.42; NNT 2). Adherence was higher with the intervention (92.5% vs 74.3%; OR 4.25). The multivariable model discriminated resolution well (AUC 0.89, 0.85–0.93). No severe adverse events occurred. Conclusion: A peer-led nutritional-education program markedly enhanced the efficacy of standard IFA, normalizing hemoglobin, replenishing iron stores and improving psychosocial well-being in anemic adolescent girls. This low-cost, scalable, school-based strategy is a promising preconception reproductive-health intervention for Indonesia and similar settings.